(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, most government agencies and private companies have sought to shape their activities based on projects. They found that by moving towards project-oriented organization, they will be able to use human and capital resources more effectively and achieve better results in accomplishing their tasks. The state of the organizations in this transition can be examined by the maturity models of the project. One of the most popular of these models is the Organizational Project Management Maturity Model (OPM3), which consists of several parts. Since this model was created by the Project Management Body of Knowledge (PMBOK), it has the most coordination with organizations that use the PMBOK standard, including Iranian organizations. Some parts of the OPM3 model, especially the assessment section, have been implemented in Iranian organizations. In this paper, the challenges of implementation of the OPM3 maturity model in Iranian petrochemical industry are discussed employing relevant experts. Finally, various strategies for these challenges are proposed.